2022
DOI: 10.1177/13623613221105085
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of parents raising children with developmental disabilities in Ethiopia

Abstract: The experiences of parents raising children with developmental disabilities have been widely researched, although most of this research comes from Western, high-income countries. In comparison, little is known about the lived experiences of parents of children with developmental disabilities in low- and middle-income countries and in Africa in particular. Parents’ lived experiences can provide insights into local conceptualizations of developmental disabilities, challenges children and their families face and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This is likely to put parents to severe economic strain. Studies conducted in Ethiopia [ 62 , 63 ] found that parents of children with neurodevelopmental disorders experience such economic challenges as financial difficulty, lack of education and training, lack of financial support and employment opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely to put parents to severe economic strain. Studies conducted in Ethiopia [ 62 , 63 ] found that parents of children with neurodevelopmental disorders experience such economic challenges as financial difficulty, lack of education and training, lack of financial support and employment opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO CST was developed using expert consultation and emerging evidence showing that, although there is a need to examine predictors, moderators and mediators of intervention effectiveness through high‐quality studies are needed 118 . Initial research on the WHO CST showed positive findings for child and caregiver outcomes and showed that the program was acceptable, relevant, and feasible 119, 120 . Community scale‐up and additional research on the WHO CST is ongoing and will probably inform future directions in CST interventions.…”
Section: Discussionmentioning
confidence: 99%
“…118 Initial research on the WHO CST showed positive findings for child and caregiver outcomes and showed that the program was acceptable, relevant, and feasible. 119,120 Community scale-up and additional research on the WHO CST is ongoing and will probably inform future directions in CST interventions.…”
Section: Favors Control Favors Treatmentmentioning
confidence: 99%
“…P. Simelane, 2020). Often, the complexities of disability, limited psycho-social support, poverty, unemployment and stigma negatively impact caregivers of children with DD, leaving them distressed and disconnected (Gladstone et al, 2018; Masefield et al, 2020; Mthombeni & Nwoye, 2018; Tekola et al, 2022). Caring for caregivers’ well-being and mental health may therefore represent a fundamental first step to support their capacity to provide nurturing care for their children.…”
Section: Introductionmentioning
confidence: 99%